To Be Is to Do: Exploring How Founder Social and Role Identities Shape Strategic Decisions in New Venture Creation Process - Magdalena Melonek (Junior Management Science (JUMS), 2020)
Founder identity is essential in entrepreneurial decision making. A number of studies have sought to examine the relationship between founder identity and venture by taking a unilateral perspective of either social identity theory or identity theory. On the basis of an exploratory single-case study conducted with a German venture from the sustainable fashion industry, this bachelor thesis integrates both theories and explores how the synergy of a founder's social and role identities influences core strategic decisions in new venture-creation process. The results obtained in this analysis suggest that 1) founders' social and role identities have different yet complementary impact on the new venture-creation process, and 2) strategic decisions shaping a venture are a result of different interplays between multiple social and role identities, where either one of the identity types dominates a decision or both identities simultaneously reinforce it. My contributions broaden the understanding on the interrelation between founder and his or her venture by expanding the focus of founder identity theory to social as well as role identities.
Keywords: 650; Sustainable entrepreneurship; entrepreneurial decision making; founder identity; social identity theory; identity theory; multi-founder ventures